2021
DOI: 10.1186/s13020-021-00461-y
|View full text |Cite
|
Sign up to set email alerts
|

Current status of traditional Chinese medicine for the treatment of COVID-19 in China

Abstract: An ongoing outbreak of severe respiratory illness and pneumonia caused by the severe acute respiratory coronavirus 2 (SARS-CoV-2) commenced in December 2019, and the disease was named as coronavirus disease 2019 (COVID-19). Soon after, scientists identified the characteristics of SARS-CoV-2, including its genome sequence and protein structure. The clinical manifestations of COVID-19 have now been established; and nucleic acid amplification is used for the direct determination of the virus, whereas immunoassays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…These practices are also applied in managing Stage 2 and Stage 3 COVID-19 patients in Malaysia. Compared to other countries such as China, the application of traditional Chinese medicine or Chinese herbal medicine such as Lianhua Qingwen and Jinhua Qinggan has also been widely studied and proven effective in treating and managing mild to moderate cases [ 40 , 41 ]. An artificial intelligence platform called “IDentif.AI” that can identify effective drug combinations that include a range of antivirals and cancer drugs to treat patients with mild to moderate disease was made available [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These practices are also applied in managing Stage 2 and Stage 3 COVID-19 patients in Malaysia. Compared to other countries such as China, the application of traditional Chinese medicine or Chinese herbal medicine such as Lianhua Qingwen and Jinhua Qinggan has also been widely studied and proven effective in treating and managing mild to moderate cases [ 40 , 41 ]. An artificial intelligence platform called “IDentif.AI” that can identify effective drug combinations that include a range of antivirals and cancer drugs to treat patients with mild to moderate disease was made available [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…More facilities and equipment such as ICU and mechanical ventilators should be readily prepared for Stage 4 and Stage 5 patients. Traditional Chinese medicine therapies which have been reported to be effective against severe COVID-19 disease could be recommended as an alternative therapy for some of the COVID-19 patients in the country to reduce their clinical symptoms [ 40 , 41 ]. Regular COVID-19 disease screening among high-risk communities such as old folks’ homes and dialysis centres should be given attention.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, we have selected Mpro and spike protein (RBD) as drug targets, because both of them are essential for viral entry and replication. Case studies reported effectiveness of traditional Chinese medicines in the containment and prevention of COVID-19 infection in China [ 9 ]. Indian medicinal plants are also well known for their medicinal properties.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, an outbreak of coronavirus disease 2019 (COVID-19) infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is still spreading and has led to an unprecedented health crisis worldwide [ 24 ]. In response to this pandemic, the Chinese government proposes that integrated TCM and WM (also known as integrated medicine) can be applied to treat pneumonia caused by SARS-CoV2 [ 25 ]. In fact, prevention, treatment, and rehabilitation of the present COVID-19 situation in China could not be separated from the extensive participation of TCM, which has proven effective for SARS-CoV-2 by clinical and laboratory studies [ 7 , 26 28 ].…”
Section: Discussionmentioning
confidence: 99%